Analisis Pemanfaatan Media Sosial dalam Strategi Pemasaran Shopee - Syifa Ananda; Safira Ade Anggreini; Sintya Grace (Jurnal Bisnis Kreatif dan Inovatif, 2025)
The development of digital technology has encouraged companies to adjust their marketing strategies, one of which is by utilizing social media. Shopee, as one of the largest e-commerce platforms in Indonesia, actively uses social media to expand its market reach, enhance its brand image, and attract consumers. This study aims to analyze how Shopee uses social media in its marketing strategy, focusing on the types of strategies used and their effectiveness in influencing consumers. The research method used is a Google form. The analysis is conducted by collecting questionnaire results from people who have filled it out and comparing them with other results. The results show that Shopee uses social media through various approaches, such as collaborating with influencers, creating creative content, and running interactive promotional campaigns on platforms such as Instagram, TikTok, and YouTube. These strategies have proven effective in increasing brand awareness, building interactions with consumers, and encouraging customer loyalty and purchasing decisions. This study concludes that social media plays an important role in supporting the success of Shopee's marketing strategy. These findings are expected to serve as a reference for e-commerce companies and other businesses in developing effective digital marketing strategies.